Respuestas

2013-05-02T11:19:20+02:00

tan x = sen x / cos x

sec x = 1 / cos x

cot x = 1 / tan x = cos x / senx

 

Sustituimos en la identidad:

[(sen x / cos x) + cos x ] / sen x = (1 / cos x) + (cos x / sen x)

 [(sen x + cos 2 x) / cos x] / sen x = (sen x + cos 2 x) / sen x cos x

 

(sen x cos 2 x) / sen x cos x = (sen x cos 2 x) / sen x cos x

 

Ambos miembros son iguales por lo que ya está demostrada la identidad

¡La mejor respuesta!
2013-05-02T16:35:45+02:00

tanx/senx + cosx/senx =

senx/cosx  + cosx/senx =

senx/1

 

senx

cosx    + cosx/senx=

senx

   1

 

Senx/senx.cosx  + cosx/senx=

 

1/cosx + cosx/senx = secx+cotx